2020
DOI: 10.1111/cxo.13016
|View full text |Cite
|
Sign up to set email alerts
|

Pattern electroretinography in patients with unilateral acute central serous chorioretinopathy

Abstract: Background To evaluate the pattern electroretinography (PERG) in patients with acute central serous chorioretinopathy (CSCR) at baseline and after spontaneous resolution. Methods A total of 32 patients (mean ± SD age: 38.8 ± 8.2 years, 71.9 per cent female) with unilateral acute CSCR and spontaneous resolution during follow‐up period were included. The unaffected eyes of the study patients comprised the control group. The best‐corrected visual acuity, PERG and optical coherence tomography findings were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…That finding is consistent with our results and proves mainly photoreceptor damage in acute CSCR cases and minor GC involvement. On the other hand, analysis of acute CSCR cases by Doguizi et al showed decreases in both P50 and N95 waves that improved but still persisted after resolution of CSCR [ 38 ]. That result indicates GC deficit even in acute CSCR.…”
Section: Discussionmentioning
confidence: 99%
“…That finding is consistent with our results and proves mainly photoreceptor damage in acute CSCR cases and minor GC involvement. On the other hand, analysis of acute CSCR cases by Doguizi et al showed decreases in both P50 and N95 waves that improved but still persisted after resolution of CSCR [ 38 ]. That result indicates GC deficit even in acute CSCR.…”
Section: Discussionmentioning
confidence: 99%